Respiratory syncytial virus A in haematological patients with prolonged shedding: premature stop codons and deletion of the genotype ON1 72-nucleotide-duplication in the attachment G gene - Tabatabai, Julia; Giesen, Nicola; Schnitzler, Paul (Clinical and diagnostic virology, 2018)
Background: Respiratory syncytial virus (RSV) can be associated with severe disease and prolonged shedding in immunocompromised patients. Objective: To investigate the genetic variability of RSV in consecutive samples of haematological patients with prolonged RSV shedding. Study design: Haematological patients at the University Hospital Heidelberg are routinely screened for respiratory viruses during winter season. In patients with prolonged RSV shedding between 2011 and 2014, Sanger-sequencing of the second hypervariable region of the RSV G gene was performed in consecutive samples. Further, deep-sequencing was performed in representative samples. Results: Patients with prolonged RSV-A shedding were analysed (n=16, mean shedding 90days, 81.2% male). Phylogenetic analysis identified RSV genotypes NA1 (2011/12) or ON1 (2012/13). In most patients (n=12/16), Sanger-sequencing of the G gene showed identical sequences over the course of the shedding period. However, in two patients with particularly long viral shedding (333 and 142days), Sanger-sequencing revealed the presence of mutations leading to premature stop codons (37 and 70 amino acids truncated) in the G gene. In one additional patient, deep-sequencing revealed variants with premature stop codons at different positions. All three patients received repeatedly intravenous immunoglobulins. Interestingly, deep-sequencing revealed also a loss of the characteristic 72-nucleotide-duplication in all analysed ON1 strains. Conclusions: Long shedding periods and lack of immune selective pressure in the immunocompromised host seems to allow the persistence of viruses stripping a part of the C-terminus of the G glycoprotein. The loss of the characteristic 72-nucleotide-duplication in RSV-A ON1 variant strains is here described for the first time.